2004
DOI: 10.1246/cl.2004.742
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N,N′-Disubstituted Urea from Ethylene Carbonate and Amine Using CaO

Abstract: Calcium oxide has been proved to be an excellent solid catalyst for the synthesis of N,N′-disubstituted ureas from ethylene carbonate and primary amines under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The synthesis of ureas from 1,3-dioxolan-2-one is a three-step process involving initial formation of a carbamate that, under appropriate reaction conditions, can be converted into an isocyanate, which then reacts with another equivalent of an amine to give the product (Scheme 20). Efficient conversion requires the presence of a base with sodium methoxide, [61] solid calcium oxide, [62] cesium carbonate, [63] and 1,5,7-triazabicyclo[4.4.0]dec-5ene [64] all being applicable. Symmetrical N,N¢-disubstituted ureas are easily accessible by this route upon reaction of 1,3-dioxolan-2-one with 2 equivalents of a primary aliphatic amine in the presence of one of the above reagents.…”
Section: Acyclic Unfunctionalized Ureasmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of ureas from 1,3-dioxolan-2-one is a three-step process involving initial formation of a carbamate that, under appropriate reaction conditions, can be converted into an isocyanate, which then reacts with another equivalent of an amine to give the product (Scheme 20). Efficient conversion requires the presence of a base with sodium methoxide, [61] solid calcium oxide, [62] cesium carbonate, [63] and 1,5,7-triazabicyclo[4.4.0]dec-5ene [64] all being applicable. Symmetrical N,N¢-disubstituted ureas are easily accessible by this route upon reaction of 1,3-dioxolan-2-one with 2 equivalents of a primary aliphatic amine in the presence of one of the above reagents.…”
Section: Acyclic Unfunctionalized Ureasmentioning
confidence: 99%
“…Scheme 20 Synthesis of Symmetrical N,N¢-Disubstituted Ureas from 1,3-Dioxolan-2one [61][62][63][64] S,S-Dimethyl dithiocarbonate represents an attractive phosgene substitute that allows facile preparation of symmetrical and unsymmetrical ureas. In an early report, it was demonstrated that treatment of S,S-dimethyl dithiocarbonate with 2 equivalents of a primary aliphatic amine in methanol at 60 8 8C for 24 hours gave the corresponding symmetrical ureas in yields of between 65 and 92%.…”
Section: Acyclic Unfunctionalized Ureasmentioning
confidence: 99%